2016
DOI: 10.1002/adma.201603326
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Hardness and Self‐Healing of Perovskite Solar Cells

Abstract: Thin-film tandem solar cells, comprising of a perovskite top junction and a radiation hard

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
237
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(250 citation statements)
references
References 40 publications
7
237
0
Order By: Relevance
“…The complete removal of solvents from the depth of the cell might prove difficult in some cases, and various solvents and deposition conditions have been reported to address this issue . Perovskites have been shown to possess some unusual material properties, including ion migration and self‐healing . The unique environment and fabrication conditions of the perovskite in C‐PSCs, along with these peculiar attributes of the material, are likely to take part in the observed cell maturation.…”
Section: Introductionmentioning
confidence: 99%
“…The complete removal of solvents from the depth of the cell might prove difficult in some cases, and various solvents and deposition conditions have been reported to address this issue . Perovskites have been shown to possess some unusual material properties, including ion migration and self‐healing . The unique environment and fabrication conditions of the perovskite in C‐PSCs, along with these peculiar attributes of the material, are likely to take part in the observed cell maturation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the extreme temperature in space could be controlled by optimizing encapsulation to guarantee device stability. More recently, it has been demonstrated that perovskites have excellent radiation hardness to high‐energy particles for space applications . However, light‐induced degradation is inevitable against its real application as light absorbers in solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…This fact is in good agreement with the high energy of the protons (68 MeV), which provide a uniform treatment of the volume of thin films. [9] The built in voltage Vbi′ = 1.25 V is determined by the extrapolation toward the interception with the voltage axis (see Equation 1). The density of uncompensated doping sources N was calculated from the slope of the linear dependence according to [13]   In our previous work [9] we have shown that the observed difference in Jsc originates purely from the proton induced darkening of the glass substrate [24] and has nothing to do with the proton damage of the perovskite active layer.…”
Section: Capacitance Characteristicsmentioning
confidence: 99%
“…[9] The radiation hardness of perovskite solar-cells was established to be about three orders of magnitude higher than that of conventional crystalline silicon (c-Si) solar cells. [10] A unique combination of the high radiation hardness with the high efficiency, the low weight thin-film architecture and the low-cost manufacturing make regular perovskite solar cells and high efficiency perovskite/Cu2InGaSe4 (CIGS) tandem solar cells attractive for operation in radioactively polluted zones and for space applications.…”
Section: Introductionmentioning
confidence: 99%